2013
DOI: 10.1155/2013/902532
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Personality Type and Acceptable Noise Levels: A Pilot Study

Abstract: Objectives. This study examined the relationship between acceptable noise level (ANL) and personality. ANL is the difference between a person's most comfortable level for speech and the loudest level of background noise they are willing to accept while listening to speech. Design. Forty young adults with normal hearing participated. ANLs were measured and two personality tests (Big Five Inventory, Myers-Briggs Type Indicator) were administered. Results. The analysis revealed a correlation between ANL and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…Consistent with this finding, Recker et al (2011) found that their results from a custom noise-tolerance questionnaire failed to accurately predict the ANL performance of 86 individuals with normal hearing and 53 individuals with impaired hearing. These findings seem to be at odds with those of Franklin et al (2013) who found significant relationships between some personality traits and response to noise (see Introduction). It should be recalled, however, that Franklin et al only tested young listeners with normal hearing.…”
Section: Effects Of Noise Sensitivity and Personalitymentioning
confidence: 81%
See 1 more Smart Citation
“…Consistent with this finding, Recker et al (2011) found that their results from a custom noise-tolerance questionnaire failed to accurately predict the ANL performance of 86 individuals with normal hearing and 53 individuals with impaired hearing. These findings seem to be at odds with those of Franklin et al (2013) who found significant relationships between some personality traits and response to noise (see Introduction). It should be recalled, however, that Franklin et al only tested young listeners with normal hearing.…”
Section: Effects Of Noise Sensitivity and Personalitymentioning
confidence: 81%
“…Using a Big Five questionnaire, Cox et al (2007) found neuroticism, agreeableness, and extraversion to be associated with a number of self-report HA outcomes. Also using a Big Five questionnaire, Franklin et al (2013) conducted a pilot study with young normal-hearing listeners to examine potential relationships between acceptance of background noise and personality traits. Their data suggested that listeners who are more open to new experiences may accept more noise, while those who are more conscientious may accept less noise.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that people emotionally unstable are overly concerned with the source of the unwanted sound and respond to it more negatively, resulting in stress. Franklin et al (2013) examined the relationship between acceptable noise level and personality. The analysis revealed a correlation between acceptable noise and openness or conscientious personality dimensions.…”
Section: Personality and Acousticsmentioning
confidence: 99%
“…Cox, Alexander and Gray (2006) found that extroversion individuals tend to report more HAs use and benefi t in all communication situations . Franklin et al (2013), demonstrated a strong relationship between extroversion personality, willingness to listen to speech in the presence of background noise, and willingness to wear HAs in older adults.…”
mentioning
confidence: 99%